Fruit-all dewaxing wipes / The Amethyst - The Amethyst, Kolej Matrikulasi Selangor (2020)
The Fruit-All Dewaxing Wipes project was implemented based on the observations of group members on the pattern of nutritious food selection by matriculation program students. Through the brainstorming process carried out, there are some major problems faced by them that lead to the emergence of the idea to produce a product realized through the Fruit-all Dewaxing Wipes project. Through observations, matriculation program students were found to quickly look lethargic by noon which affected the PdP process carried out. This condition leads to the tendency of students to take unhealthy snacks to cover the stomach which leads to health problems. Students who like to take fruit as a snack are found not to wash the product thoroughly before eating it in addition to lack of awareness and concern related to the content of harmful chemicals in the food taken.